A Fuzzy Biomechanical Model with H2 Control System for Sit-to-Stand Movement - Mughal, A.M.; Iqbal, K. (2006 American Control Conference, 2006)
Biomechanical movements have been subject of interest for several centuries to different researchers for various aspects. Physiologically human biomechanical sit to stand movement can be defined in different phases and regions. A four link biomechanical model of human stable movement is used to develop the local linear models for each phase from sitting on chair to an upright standing position. These local models are then integrated into a fuzzy model with Gaussian membership function. The knee flexion angle during sit to stand movement provides the criterion for determining the weights of fuzzy membership functions. H 2 dynamic optimal controller is designed for each local linear model and integrated with the fuzzy model. The joint's torque or inputs are computed by using linear fuzzy model based H 2 controller for linear and nonlinear biomechanical models. A reference trajectory is introduced to track the knee flexion angle error for smooth and physiological relevant sit to stand transfer. Simulation results of angular profiles and kinematics variables demonstrate the applicability of the fuzzy modeling with H 2 full order and reduced order controller for the biomechanical sit to stand movement